The Pesantren Based Madrasah Model: Authority, Curriculum Policy, and Standardization of Student Outcomes - Ridha Kurniawan; Hufri; Lala Hariani (Journal of Contemporary Islamic Education, 2026)
Pesantren based madrasahs still face institutional dualism in terms of authority structures, curricula, and student outcomes, which remain unintegrated between the pesantren system and state requirements. This situation highlights the need for an analytical model that comprehensively explains the interrelationships among these three aspects. This study aims to analyze pesantren-based madrasah models with a focus on the relationship between authority structures, curriculum policies, and the standardization of student outcomes. This study employs a qualitative case study approach conducted from January to March 2026. Data were collected through in-depth interviews, observations, and documentation involving madrasah principals, pesantren leaders, vice principals for curriculum, Islamic Religious Education teachers, and administrative staff. Data analysis employed an interactive model involving data reduction, data presentation, and drawing conclusions, with triangulation of sources and techniques used to test data validity. The research findings indicate that the authority structure is dual in nature a blend of traditional and rational-legal authority that forms a hybrid institutional framework. This structure produces an integrative curriculum policy through negotiations between the state and Islamic boarding schools; however, the evaluation system remains fragmented, resulting in dualistic student outcomes academic and religious. The novelty of this study lies in a model that positions the authority structure as a determinant of curriculum policy and the curriculum as a determinant of student outcomes. This study underscores the importance of integrating the curriculum and the evaluation system to produce graduates who are well-rounded in academic, religious, and character competencies.